Read All About : DANCE - Mitchinson, Christy (Read All About It!, 2023)
"There is a dance style for everyone! Ballerinas sometimes dance on tiptoe. Tap dancers wear special shoes that make tapping sounds as they move. Some dancers make up their own moves while others follow a routine. Find out all about dance styles, equipment, studios, and more in this fact-filled book. Stunning photos give readers an up-close look at all kinds of dance, from hip-hop to Brazilian samba."